The Industrialisation of Zimbabwe - Past, Present and Future - Stoneman, Colin (Afrika Focus, 1990)
In this paper I look at Zimbabwe's moderately successful industrialisation experienHce, past, present and future. The lessons that can be drawn from this experience in comparison with what has happened in other countries, both more and less succesful, are: that there is a need for an intelligent state role; that both import substitution and export substitution are necessary; that emphasis on industry need not and must not be mean neglect of agriculture; and that the key problem is how to avoid enclave industrialisation which services urban elites but neglects the rest of the country and the region.